2018
DOI: 10.1097/wnp.0000000000000428
|View full text |Cite
|
Sign up to set email alerts
|

Electrographic and Clinical Natural History of Lateralized Periodic Discharges

Abstract: LPDs lead to markers of epileptogenicity in around 18% of patients. One-third of the study population developed epilepsy. rEEG findings were not found to be good indicators of epilepsy development in our small, retrospective study limited by its sampling bias. Indiscriminate, long-term use of AEDs in these patients is a concerning finding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 20 publications
2
18
1
Order By: Relevance
“…Interestingly in our study, more than 1.5 years after being discharged on AED, two‐thirds (65.7%) of cases were still taking at least one AED. Similar trends have been noted previously as well . AEDs status at discharge was not used in statistical modeling because it was found to be highly collinear with the group status (95% of cases were on AEDs at discharge as compared to only 16% of controls).…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Interestingly in our study, more than 1.5 years after being discharged on AED, two‐thirds (65.7%) of cases were still taking at least one AED. Similar trends have been noted previously as well . AEDs status at discharge was not used in statistical modeling because it was found to be highly collinear with the group status (95% of cases were on AEDs at discharge as compared to only 16% of controls).…”
Section: Discussionsupporting
confidence: 55%
“…Previously, we have investigated the development of new‐onset epilepsy after patients were found to have electrographic seizures (NCS/NCSE), LPDs, or generalized periodic discharges (GPDs) on cEEG. In these retrospective, medical records review‐based studies, we have shown that the risk of epilepsy development is determined by the type of cEEG findings . Building on this work, we designed a matched, parallel cohort study with the specific aims of finding the impact of highly epileptic cEEG features – that is, electrographic seizures and LPDs – on the risk of epilepsy development after acute hospitalization.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, 30% of patients in the NP/NE group were discharged on AEDs as well. Previously, we found similar high rates of discharge on AEDs in a different study population where we tried to map the long‐term, electrographic natural history of LPDs . In that study as well, close to one‐third (31%) of patients with LPDs developed epilepsy during a mean follow‐up of 19.8 ± 9.9 months …”
Section: Discussionsupporting
confidence: 52%
“…predicting new onset epilepsy among patient with periodic patterns (LPDs or GPDs) on cEEG in a different study population where we tried to map the long-term, electrographic natural history of LPDs. 22 In that study as well, close to one-third (31%) of patients with LPDs developed epilepsy during a mean follow-up of 19.8 ± 9.9 months. 22 Several common traits for epileptogenesis across the etiological spectrum of symptomatic epilepsies are currently being recognized.…”
Section: T a B L E 4 Adjusted Analyses Formentioning
confidence: 69%
See 1 more Smart Citation